The Institutional Leaders in Universities: A Framework for Improving Competency Assessment - Abdullah, Norazharuddin Shah; Ghani, Erlane K; Jais, Ismie Roha Mohamed; Yahya, Yazrina (Journal of Ecohumanism, 2024)
This study describes the process of creating and improving a leadership competency framework within an organisation responsible for identifying potential leaders in universities. Specifically, this study assesses the leadership competency framework created in 2015 and its current relevance. Based on the focus group discussions, this study emphasises the need to refine the existing leadership competencies framework to accurately represent the current state of leadership at universities. The participants unanimously agreed to retain all clusters with minor changes. Specifically, the participants suggested that self-management should replace self-confidence to improve personal effectiveness. The leaders must have the ability to manage stress efficiently and maintain a stable state of mind. This study indicates participants understood diversity and flexibility, and leaders must adapt and use others’ skills, especially in certain circumstances. The ability to adjust behaviour and ideas to environmental changes fosters inventiveness, critical thinking, and methodological challenge. In addition, the leaders must have a friendly and highly skilled demeanour. The participants also suggested introducing five additional assessment tools to evaluate the competence of future leaders. The five instruments include the 180-degree assessment, the 360-degree leadership assessment, the psychometric tests for IQ and EQ, the psychometric tests for personality, and the scenario planning analysis. The findings of this study provide an improved structure for identifying a competent leader who is exceptionally well suited to universities’ unique demands.